Análise de séries temporais multivariadas via Wavelet - Mori, Matheus Kengi (2023)
After the mid-1980s, wavelet theory quickly spread to many fields. Although wavelet analysis has the ability to decompose data into various time scales and to deal with nonstationary data and time location, this methodology has not become a popular application in economics. This course completion work will use wavelet transformation, wavelet decomposition and wavelet coherence methodologies to analyze the correlation between four financial series, such as the Dow Jones, S&P500, IBOVESPA and Bitcoin. In order to enhance economic analysis, a technique that is little used in the field of economics.